Acute Effect of Transcutaneous Electroacupuncture on Globus Pharyngeus: A Randomized, Single-Blind, Crossover Trial - Zhou, Wencong; Deng, Qi; Jia, Lin; Zhao, Hanbing; Yang, Meng; Dou, Guoyuan; He, Zijian; Guo, Wanwei (Frontiers in Medicine, 2020)
Background: Acupuncture points are commonly used by Traditional Chinese Medicine to treat throat discomfort. Transcutaneous electroacupuncture (TEA) is a new therapy combining transcutaneous electrical nerve stimulation with meridian theory. The efficacy and mechanism of Transcutaneous electroacupuncture for globus pharyngeus has not been reported. The aim of our study was to explore the effect and possible mechanisms of TEA at CV22/LI3/LU11/ST36 for patients with globus. Methods: A total of 80 patients with globus pharyngeus were randomly allocated into eight groups. The intervention order in Groups A1/B1/C1/D1 was firstly TEA at CV22/LI3/LU11/ST36 during the first period and sham-TEA in the second period. For participants in Groups A2/B2/C2/D2, the intervention order was the reverse. Before the test, the participants were asked to complete the Glasgow Edinburgh Throat Scale (GETS), visual analog scale (VAS), and the Hamilton Rating Scale Anxiety/Depression and were then asked to test and measure the heart rate variability and serum hormone levels of SP and NPY. At the end of the second period, these tests were manipulated again. Results: D-values of GETS and VAS following stimulation at CV22/LU11 were significantly higher than those of sham-stimulating (CV22: 13.5 ± 13.09 vs. 1 ± 9.68, P <0.002; LU11: 17 ± 10.31 vs. 9 ± 9.68, P = 0.011). Heart rate variability, SP, and NPY were showed a significant difference in LU11 stimulation compared to other acupuncture points (P all <0.05). Conclusion: Stimulation at CV22/LU11 significantly improved symptoms of globus. The results indicated that symptoms may be improved by stimulating the parasympathetic nervous system and secreting SP and NPY when stimulating at LU11. For CV22, it may improve symptoms by direct action on the throat. Stimulating at CV22/LU11 may be a potential therapy for treating globus.